Boilerplate : practical clauses - Christou, Richard (London : Sweet & Maxwell, 2012)
This compendium of boilerplate clauses in common use also features detailed analytical commentary on each clause, together with advice on its application. The book also takes account of recent case law where applicable and comes with a CD-rom containing all the clauses for ease of access to readers
Accompanied by CD-ROM in pocket inside back cover
Includes index
Previous ed.: 2010
Keywords: Clauses (law) -- England; Clauses (law) -- Wales; Contracts -- England; Contracts -- Wales